2016
DOI: 10.1038/srep37324
|View full text |Cite
|
Sign up to set email alerts
|

YY1 binding association with sex-biased transcription revealed through X-linked transcript levels and allelic binding analyses

Abstract: Sex differences in susceptibility and progression have been reported in numerous diseases. Female cells have two copies of the X chromosome with X-chromosome inactivation imparting mono-allelic gene silencing for dosage compensation. However, a subset of genes, named escapees, escape silencing and are transcribed bi-allelically resulting in sexual dimorphism. Here we conducted in silico analyses of the sexes using human datasets to gain perspectives into such regulation. We identified transcription start sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 72 publications
4
34
0
Order By: Relevance
“…Nevertheless, based on these epigenetic signatures, several groups have concluded that escape is often regulated via promoter-proximal sequences [45,69]. Consistent with this idea, YY1 motifs and ChIP-seq peaks are overrepresented at human escapee start sites and are proposed to facilitate escape [36]. Most ATAC-seq accessible sites on the inactive X in mouse identify CTCF sites [69], adding to accumulating evidence that CTCF, a multifunctional protein with broad roles in gene expression and chromosome architecture [71], is an important player in escape gene regulation.…”
Section: (C) Sexual Dimorphismmentioning
confidence: 50%
See 1 more Smart Citation
“…Nevertheless, based on these epigenetic signatures, several groups have concluded that escape is often regulated via promoter-proximal sequences [45,69]. Consistent with this idea, YY1 motifs and ChIP-seq peaks are overrepresented at human escapee start sites and are proposed to facilitate escape [36]. Most ATAC-seq accessible sites on the inactive X in mouse identify CTCF sites [69], adding to accumulating evidence that CTCF, a multifunctional protein with broad roles in gene expression and chromosome architecture [71], is an important player in escape gene regulation.…”
Section: (C) Sexual Dimorphismmentioning
confidence: 50%
“…An interesting exception is that the pseudoautosomal genes in PAR1, despite identity to homologues on the Y chromosome, are expressed at higher levels in males [8]. A recent variation of this approach compares male/female cap analysis of gene expression (CAGE) datasets of the 5 0 end of transcripts [36] and expands and refines human XCI maps, as alternative transcript start sites can have different XCI status [37]. A clear advantage to femalebiased escape gene analyses is the ability to evaluate all expressed X genes in each sample.…”
Section: (C) Sexual Dimorphismmentioning
confidence: 99%
“…YY1 binding adjacent to CTCF has also been reported at DXZ4 (Moseley et al. 2012; Chen et al. 2016) and the FIRRE locus (Yang et al.…”
Section: Resultsmentioning
confidence: 99%
“…This motif occurs 2.5 times more frequently in the group of escapees and early reactivated genes (n=20, 57 promoters), than in the group of late and very late genes (n=7, 49 promoters). YY1 is associated with escapees in human and has previously been described to be co-bound to the same binding sites as MYC in mouse ESCs 42,43 . The precise roles of the MYC proteins and YY1 in relation to Xp gene activity merits future exploration.…”
Section: Discussionmentioning
confidence: 91%